Environmental and economic regulation of sustainable spatial agroforestry. (30th April 2021) - Prokopenko, Olha; Mishenin, Yevhen; Mura, Ladislav; Yarova, Inessa
The article describes the strategic orientations of environmental and economic regulation of sustainable agroforestry under the conditions of anthropogenic and agro-natural environment formation. The necessity to determine the territorial agroforestry potential for further formation of the agroforestry natural capital and the forest reclamation planning of agricultural landscapes is discussed. The system and mechanisms of the forest environment and economic regulation of sustainable spatial agroforestry in terms of the motive factors' formation and creating linear-type forest shelterbelts by agribusiness entities require the agroforestry reclamation cadaster. The methodology of environment and economic assessment of creating forest shelterbelts from the perspectives of the ecosystem service economy has been improved. Some features of determining the 'total economic value' of forest protective belts have been considered in this article. A system of strategic targets (production, economic, environmental, and social) for environmental and economic regulation of the spatial agroforestry has been proposed.